Firing Stability of Rarefaction Wave Gun Based on Virtual Prototype - 支建庄 于贵波 苏续军 洪青 邓士杰 (东华大学学报（英文版）, 2016)
The dynamics characteristics of rarefaction wave gun（ RAVEN） in launching are studied. Based on its characteristics of structure and interior ballistics, the launch dynamic model and virtual prototype of RAVEN are established. After simulating and solving by ADAMS software, through comparison RAVEN to conventional gun,influences of some structural parameters on firing stability are acquired. Optimization analysis of structural parameters of gun based on analysis of the firing stability is done. It puts forward the theoretic basis for improving firing stability and security.